Reassessing the Role of Breast Self-Examination in Breast Cancer Screening: Insights from a Five-Year Observational Study in Kurdistan, Iraq - Ghalib, Hawar Ali (Journal of Sulaimani Medical College, 2025)
Background: Breast self-examination (BSE) and mammography are commonly advocated screening methods for the early detection of breast cancer (BC), particularly in low-resource settings. However, the effectiveness of BSE in reducing morbidity and mortality remains controversial. Therefore, the aim of current study is to evaluate the association between routine breast self-examination and mammography with the stage at diagnosis of breast cancer, and to determine which screening modality is more likely to facilitate early detection. Methods: A retrospective observational study was conducted on 429 women diagnosed with primary BC at the Breast Diseases Treatment Clinic, Shar Teaching Hospital, Sulaimaniyah, Iraq, between January 2017 and December 2021. Sociodemographic and clinical data were collected through validated questionnaires and medical records. Associations between tumor stage and screening practices (BSE and mammography), along with other variables, were assessed using Pearson’s Chi-square test. Results: The mean age of participants was 49.6 ± 11.8 years. Most women were urban residents, housewives, and had no family history of BC. A significant association was found between mammography and early-stage diagnosis (p = 0.016), whereas BSE showed no such association (p = 0.982). Other factors, including occupation, family history, smoking, and previous surgical or biopsy history, were not significantly associated with tumour stage. Conclusion: Routine mammography was significantly associated with earlier detection of breast cancer, whereas BSE did not show a measurable benefit. These findings underscore the importance of promoting mammography as a primary screening tool and highlight the limitations of relying on BSE alone for early detection in clinical practice.
Keywords: Breast selfexamination; breast cancer; mammography; screening; tumor stage; early detection